1998
DOI: 10.1093/oxfordjournals.alcalc.a008368
|View full text |Cite
|
Sign up to set email alerts
|

REDUCTION OF VOLUNTARY ETHANOL INTAKE IN ETHANOL-PREFERRING sP RATS BY THE CANNABINOID ANTAGONIST SR-141716

Abstract: The present study assessed the efficacy of the cannabinoid CB1 receptor antagonist, SR-141716, in reducing voluntary ethanol intake in selectively bred Sardinian alcohol-preferring (sP) rats. Ethanol (10%, v/v) and food were available in daily 4 h scheduled access periods; water was present 24 h/day. The acute administration of a 2.5 and a 5 mg/kg dose of SR-141716 selectively reduced ethanol intake, whereas a 10 mg/kg dose of SR-141716 reduced to a similar extent both ethanol and food intake. These results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
146
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(163 citation statements)
references
References 9 publications
16
146
1
Order By: Relevance
“…This result is in line with previous studies showing reduced voluntary alcohol intake or operant self-administration in rats by SR 141716A (Arnone et al, 1997;Colombo et al, 1998b;Rodriguez et al, 1999). Consistently with these, CB1 knockout mice have shown greatly reduced ethanol consumption and preference (Hungund et al, 2003;Wang et al, 2003;Naassila et al, 2004).…”
Section: Systemic and Pfc Injections Of Sr141716a Reduce Ethanol Selfsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is in line with previous studies showing reduced voluntary alcohol intake or operant self-administration in rats by SR 141716A (Arnone et al, 1997;Colombo et al, 1998b;Rodriguez et al, 1999). Consistently with these, CB1 knockout mice have shown greatly reduced ethanol consumption and preference (Hungund et al, 2003;Wang et al, 2003;Naassila et al, 2004).…”
Section: Systemic and Pfc Injections Of Sr141716a Reduce Ethanol Selfsupporting
confidence: 93%
“…Studies using blockade (Arnone et al, 1997;Rodriguez et al, 1999;Colombo et al, 1998b) or genetic inactivation of CB1 receptors (Hungund et al, 2003;Wang et al, 2003;Naassila et al, 2004) imply endocannabinoid signaling in regulation of ethanol self-administration. Brain expression profiling further points to the possibility that dysregulated expression of endocannabinoid genes, and signal transduction genes under their control, could contribute to high alcohol preference (Rimondini et al, 2002;Arlinde et al, 2004;Derkinderen et al, 2001).…”
Section: Differences In Endocannabinoid Transmission Between Aa and Amentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased rewarding effects of ethanol in CB 1 À/À mice might therefore be related to alteration of ethanol-induced dopamine release via CB 1 receptors in the mesocorticolimbic reward pathway. Recent observations have shown that the endogenous cannabinoid system facilitates the perception or the effects of positive reinforcers such as electrical brain stimulation (DerocheGamonet et al, 2001) and drugs of abuse (Chaperon et al, 1998;Colombo et al, 1998). The lack of morphine selfadministration in CB1 À/À mice was also associated with the inability of morphine to stimulate dopamine release in the nucleus accumbens (Mascia et al, 1999), as observed for ethanol (Hungund et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, studies have shown that the CB 1 receptor antagonist SR141716A reduces alcohol intake (Arnone et al, 1997;Colombo et al, 1998;Rodriguez de Fonseca et al, 1999) and the motivation to consume alcohol in a progressive ratio paradigm in rats, while a CB 1 receptor agonist increased the motivation to consume alcohol alcohol in a progressive ratio paradigm . In addition, ethanol (0.5-2.0 g/kg) has been shown to decrease operant responding to a greater extent in CB 1 À/À mice than in wild-type mice, suggesting a possible role of CB 1 receptor in the rate disruptive effects of ethanol (Baskfield et al, 2004).…”
Section: Introductionmentioning
confidence: 99%